Peran Guru Sekolah Minggu dalam Membangun Karakter Anak Sekolah Minggu di Era 4.0 - Ipiana; Reni Triposa; Gloria Gabriel Lumingkas (Institut Agama Kristen Negeri Kupang, 2021)
The Industrial Revolution 4.0 has brought changes in various aspects of human life. Among these is the education system. The question is, what components of education are affected, and how to respond to these implications? This paper aims to explain the changes that must be made in schools so that human resources produced by various educational institutions can compete and contribute globally. Through literature review and content analysis, the discussion shows that current and future curriculum development must complement students' abilities in the academic dimension, life skills, live together, and think critically and creatively. Other invisible skills like interpersonal skills, global-minded citizens, and literacy of the media and information available. The curriculum must also be able to shape students with an emphasis on the field, referring to ICT-based learning, the internet of things, big data and computers, as well as entrepreneurship and internships. The competencies that must be possessed by teachers are educational competence, competence for technological commercialization, competence in globalization, competence in future strategies, and competence counselor. In addition to these competencies, teachers also need to have a friendly attitude with technology, collaboration, be creative and take risks, have a good sense of humor, and teach holistically. Schools and teachers must consider the open learning platform in deciding how to organizing education and learning.